2002
DOI: 10.1053/jhep.2002.36993
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis and disease progression in hepatitis C

Abstract: The progression of fibrosis in chronic hepatitis C determines the ultimate prognosis and thus the need and urgency of therapy. Fibrogenesis is a complex dynamic process, which is mediated by necroinflammation and activation of stellate cells. The liver biopsy remains the gold standard to assess fibrosis. Scoring systems allow a semiquantitative assessment and are useful for cross-sectional and cohort studies and in treatment trials. The rate at which fibrosis progresses varies markedly between patients. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
159
1
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(187 citation statements)
references
References 66 publications
(117 reference statements)
4
159
1
23
Order By: Relevance
“…However, in paired liver biopsies, elevated ALT levels were associated with progression of fibrosis. 1113,14 Serum ALT was not predictive of development of clinical outcomes, however the AST/ALT ratio was predictive. 76 Patients with elevated serum ALT levels are also found to have increased risk for hepatocellular carcinoma.…”
Section: Factors That Influence the Outcome Of Chronic Hepatitis Cmentioning
confidence: 84%
“…However, in paired liver biopsies, elevated ALT levels were associated with progression of fibrosis. 1113,14 Serum ALT was not predictive of development of clinical outcomes, however the AST/ALT ratio was predictive. 76 Patients with elevated serum ALT levels are also found to have increased risk for hepatocellular carcinoma.…”
Section: Factors That Influence the Outcome Of Chronic Hepatitis Cmentioning
confidence: 84%
“…36 On the contrary, HCV, primary biliary cirrhosis, and autoimmune hepatitis are more insidious in nature, resulting in slowly progressive fibrosis. 37,38 Probably due to this unsatisfactory accuracy of M2BP, the combination of WFA + -M2BP and LS could not enhance the overall accuracy in predicting all fibrosis stages in comparison to LS (all P  > .05). Apart from cross-sectional analysis, which appeared unsatisfactory, we similarly explored the prognostic value of WFA + -M2BP from a longitudinal aspect.…”
Section: Discussionmentioning
confidence: 96%
“…A study of hemophiliacs showed that 32% exhibited more than 2 kPa of regression during 3.7 years of follow-up [21]. Among hepatitis B patients, Castera et al [24] reported that 81% (9/11) with an initial LSM value of >7.2 kPa regressed to normal values during 22 months of follow-up, and Kim et al [25] reported that 30% (34/114) of patients with F3+ in biopsy regressed more than 30% during 13 months. For comparison, studies using repeated biopsy have reported that up to 24% exhibited decreasing fibrosis during 3–4 years of untreated follow-up [24][26].…”
Section: Discussionmentioning
confidence: 99%